The Analysis of Factors Influencing Rice Imports in Indonesia - Septia Annisa Isnaini; Pawana Nur Indah; Dona Wahyuning Laily (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Rice is an essential commodity in Indonesian society's socio-economic life. This study aimed to determine the influence of rice imports in Indonesia from 2013 to 2022 and the implications of government policy in Indonesia. Data from the Indonesian Central Statistics Agency (BPS) spanning 2013 to 2022 was obtained as secondary information. The method applied involves using dummy variables in multiple linear regression analyses, classical assumption tests, and multiple linear regression analyses. The variables used in this analysis are rice production (X1), rice price (X2), population (X3), consumption (X4), land area (X5), exchange rate (X6) and rice imports (Y). The study outcomes obtained: simultaneously, the variables rice production, rice price, population, consumption, land area, and exchange rate affect rice imports and partially have a meaningful positive and negative effect on rice imports. The results of this research also show that simultaneously, the rice production variable on the dummy variable implementing the rice import policy has a significant influence on rice imports in Indonesia, the rice price variable on the dummy variable implementing the rice import policy has a meaningful influence on rice imports in Indonesia, simultaneously the population variable on dummy variable implementation of rice import policy has a meaningful influence on rice imports in Indonesia, simultaneously rice consumption variable on dummy variable implementation of rice import policy has a significant influence on rice imports in Indonesia, simultaneously land area variable on dummy variable implementation of rice import policy has a meaningful influence on rice imports in Indonesia. Simultaneously, the exchange rate variable on the dummy variable implementing the rice import policy has a meaningful influence on rice imports in Indonesia.